Dietary patterns and greenhouse gas emissions: a household-level analysis in Hue City, Vietnam - Nguyen, Thi Ngoc Thao; Tran, Anh Tuan; Nguyen, Ngoc Yen Nhi (Hue University Journal of Science: Natural Science, 2025)
This study examines the relationship between food consumption at the household level and greenhouse gas emissions in Hue City, Vietnam, using a survey of 400 households and emission factors derived from Life Cycle Analysis. The study underscores the significant contribution of household food consumption patterns to greenhouse gas emissions, with animal-based products, particularly beef and seafood, the primary drivers because of their high emission factors. In 2023, the city’s households generated around 3,068,534 tons of CO₂e from food consumption, highlighting the urgent need for dietary shifts toward plant-based foods to mitigate environmental impact. Additionally, the substantial food waste of 23,658 tons per year—caused by unplanned food shopping, poor meal planning, and improper storage—results in greenhouse gas emissions of 21,055 tons of CO₂e. The reliance on traditional markets for locally sourced food offers a positive note, as it reduces transport-related emissions, but current consumption and waste management practices remain unsustainable. The study argues for promoting plant-based diets, improved food waste management strategies, increased awareness of sustainable consumption, improved food systems, and comprehensive education on climate-resilient practices. These results highlight gaps in the policy framework of Hue City and other fast urbanising cities while aiding in formulating climate mitigation and sustainability policies for Vietnam.